The Effect Methods of Asking Questions and Getting Answers on Outcomes of Learning PPKn Grade IV SDN 104181 Right Sungal - Sri Hartati Saragih (Berpusi Publishing, 2025)
This research is motivated by the low learning outcomes of PPKn students in grade IV at SDN 104181 Sunggal Kanan which is caused by several things, one of which is that PPKn teachers still use conventional learning methods so that students tend to be passive in learning activities. This study aims to find out and describe how the learning outcomes of PPKn students in grade IV in the experimental class at SDN 104181 Sunggal Kanan after the application of the method of giving questions and getting answers. This method is a quantitative data processing method with a sampling technique using total sampling where the entire population can be sampled amounting to 51 students. The independent variable is the method of giving questions and getting answers, while the dependent variable is student learning outcomes. The data collection process uses a content grid instrument given to students in the control class and the experimental class which is then analyzed using SPSS software version 27. The results of the t-test (Independent Sample T-test) show that there is an influence of the method of giving questions and getting answers on students' PPKn learning outcomes with a sig value. 0.000 < (less) than the significance level (α) = 0.05, then Ha is accepted and H0 is rejected. It can be concluded that there is an influence of the learning method that provides questions and gets answers on the learning outcomes of PPKn students in grade IV of SDN 104181 Sunggal Kanan.